Datasets of a stormwater treatment train facility consisting of a gross pollutant trap and biofilters/sand filter in Sundsvall, Sweden - Beryani, Ali; Flanagan, Kelsey; Viklander, Maria; Blecken, Godecke-Tobias (Luleå University of Technology, 2024)
The data were collected from a stormwater treatment train facility in Sundsvall, Sweden. The facility consists of a gross pollutant trap (GPT) followed by three parallel biofilter cells: a vegetated, chalk-amended biofilter (BFC or F1), a non-vegetated sand filter (SF or F2), and a vegetated biofilter (BF or F3).
One of the objectives of our research project was to assess and monitor stormwater quality received from a major road catchment (incl. E4 highway bridge in Sundsvall) and also evaluate the performance of the various sections of the treatment train in removing organic micropollutants from the stormwater in terms of both inter- and intra-event variability.

The file named "StormwaterRunoffQualityData_SND.csv" contains event mean concentration (EMC) data on stormwater samples collected from 8 rain events (coded by A to H) in one year between September 2020 and September 2021. The samples have been analyzed for organic micropollutants and global water quality parameters (42 parameters in total). EMCs have been mathematically generated by a Monte-Carlo simulation from measured concentrations in sub-samples collected during each event. The data elaborate on the generated distribution for each EMC with Q2.5, Q50, and Q97.5 percentiles and standard deviation from the mean. Besides, the number of detected and non-detected (censored) data of sub-samples are mentioned. The list of all pollutants and their abbreviations are included in the documentation file named "StormwaterRunoffQualityData_SND.docx". Stormwater flow data are also presented in the file "VolumeData_Stormwater_SND.csv".

The file named "TreatmentTrainQualityData_SND.csv" presents event mean concentration (EMC) data not only for the stormwater runoff quality but also for the treated stormwater in the GPT-biofilter/sand filter treatment train downstream of the catchment. In addition to the untreated stormwater runoff as the system's inflow (SW), EMCs have been presented for 4 more sampling points: GPT outflow (GPT), vegetated, chalk-amended biofilter outflow (BFC), non-vegetated sand filter (SF), and vegetated biofilter outflow (BF). For this part of the research, a total of 11 rain events (coded by A to K) were covered from Sep. 2020 until Sep. 2021. The samples have been analyzed for organic micropollutants and other conventional water quality parameters (42 parameters in total). EMCs have been mathematically generated by a Monte-Carlo simulation from measured concentrations in sub-samples collected during each event. The data present a distribution for each EMC with Q2.5, Q50, and Q97.5 percentiles and standard deviation from the mean. The number of detected and non-detected (censored) data of sub-samples is also mentioned. The list of all pollutants and their abbreviations are included in the documentation file named "TreatmentTrainQualityData_SND.docx". Flow data are also presented in the file "VolumeData_Treatment train_SND.csv".

The file entitled "Intra-event Data_SND.csv" includes intra-event concentration data for stormwater runoff and effluents of the GPT-biofilter/sand filter treatment train. These data represent the concentrations measured for the subsamples taken at an chronological order (subsample #no. and time in the file) during each event. The corresponding flow volume passed (in m3 and % of total volume) at a certain sampling point are also included in the file. A total of 11 rain events (coded by A to K) were covered between Sep. 2020 and Sep. 2021 on the sampling dates mentioned in the file.

Uppgifterna samlades in från en reningsanläggning med flera reningssteg för dagvatten i Sundsvall, Sverige. Anläggningen består av en grov föroreningsfälla (GPT) följd av tre parallella biofilterceller: ett vegeterat, kritomvandlat biofilter (BFC eller F1), ett icke-vegeterat sandfilter (SF eller F2) och ett vegeterat biofilter (BF eller F3).
Ett av syftena med vårt forskningsprojekt var att bedöma och övervaka dagvattenkvaliteten från ett större vägavrinningsområde (inkl. motorvägsbro E4 i Sundsvall) och även utvärdera hur de olika sektionerna av reningsanläggningen presterar när det gäller att ta bort organiska mikroföroreningar från dagvattnet i termer av både inter- och intra-event variabilitet.

Filen med namnet "StormwaterRunoffQualityData_SND.csv" innehåller data för händelsemedelkoncentration (EMC) på dagvattenprover som samlats in från 8 regnhändelser (kodade av A till H) under ett år mellan september 2020 och september 2021. Proverna har analyserats för organiska mikroföroreningar och globala vattenkvalitetsparametrar (42 parametrar totalt). EMC:er har matematiskt genererats av en Monte-Carlo-simulering från uppmätta koncentrationer i delprover som samlats in under varje händelse. Datan utvecklar den genererade fördelningen för varje EMC med Q2.5, Q50 och Q97.5 percentiler och standardavvikelse från medelvärdet. Dessutom nämns antalet upptäckta och icke-upptäckta (censurerade) data för delprover. En lista med alla olika föroreningar och deras förkortningar finns inkluderade i dokumentationsfilen ”StormwaterRunoffQualityData_SND.docx”.

I filen med namnet "TreatmentTrainQualityData_SND.csv" presenteras inte bara händelsemedelkoncentrationen (EMC) för dagvattenavrinningens kvalitet, utan också för det behandlade dagvattnet i reningssystemet nedströms från avrinningsområdet, vilket inkluderar en försedimenteringsanläggning (GPT) och ett sandfilter. Förutom att dagvattenavrinningen utgör systemets inflöde (SW), har händelsemedelkoncentrationen (EMC) från fyra andra provtagningspunkter också presenterats: försedimenteringsanläggningens utflöde (GPT), växtbevuxet, kritomvandlat biofilterutflöde (BFC), icke-växtbevuxet sandfilter (SF) och växtbevuxet biofilterutflöde (BF). Den här delen av undersökningen täcker in 11 regnhändelser (kodade A till K) under perioden sep 2020 och sep 2021. Proverna har analyserats för organiska mikroföroreningar och globala vattenkvalitetsparametrar (42 parametrar totalt). EMC:er har matematiskt genererats av en Monte-Carlo-simulering från uppmätta koncentrationer i delprover som samlats in under varje händelse. Datan utvecklar den genererade fördelningen för varje EMC med Q2.5, Q50 och Q97.5 percentiler och standardavvikelse från medelvärdet. Dessutom nämns antalet upptäckta och icke-upptäckta (censurerade) data för delprover. En lista med alla olika föroreningar och deras förkortningar finns inkluderade i dokumentationsfilen ” TreatmentTrainQualityData_SND.docx”.

Filen med titeln "Intra-event Data_SND.csv" inkluderar intra-event koncentrationsdata för dagvattenavrinning och avloppsvatten från GPT-biofilter/sandfilterbehandlingsanläggningen. Dessa data representerar de uppmätta koncentrationerna för delproven tagna i en kronologisk ordning (delprov #nr. och tid i filen) under varje händelse. Motsvarande flödesvolym som passerat (i m3 och % av total volym) vid en viss provtagningsplats ingår också i filen. Totalt 11 regnhändelser (kodade av A till K) täcktes mellan september 2020 och september 2021 på de provtagningsdatum som nämns i filen.
Dataset från en dagvattenreningsanläggning med flera reningssteg vid E4, Sundsvall: försedimentering och biofilter/sandfilter
Keywords: PETROLEUM HYDROCARBONS; biological contamination; biologisk förorening; phenol; fenol; pollution control technology; föroreningsbekämpande teknik; polycyclic aromatic hydrocarbon; polycykliskt aromatiskt kolväte; biodegradable pollutant; biologiskt nedbrytbar förorening; water pollutant; vattenförorening; water pollution prevention; förebyggande av vattenförorening; storm water; dagvatten; biofilter; biofilter; Stormwater runoff; dagvattenavrinning; event mean concentration; händelsemedelkoncentration; bioretention; bioretention; sand filter; sandfilter; Construction Management; Byggprocess och förvaltning; Infrastructure Engineering; Infrastrukturteknik; Water Engineering; Vattenteknik